2018
DOI: 10.1177/1365480218783793
|View full text |Cite
|
Sign up to set email alerts
|

What urban parents want: A parent network’s negotiation of school choice and advocacy efforts in underserved city schools

Abstract: This community-based participatory research study examined the perspectives of parent participants in an organized parent network in Detroit seeking the best school options for their children entering Kindergarten within city boundaries. Their residency and school choices have emerged against the grain of public schools that have racially charged histories and decades of residential mobility trends. Examined are ways in which the parent network researched, collaborated, and made informed public, private, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 4 publications
1
11
0
Order By: Relevance
“…According to the conducted survey, a slightly different response breakdown was obtained based on a variety of obtained factors. When families preferred in-depth knowledge, they confirmed the importance of the quality of successful schools which was manifested by meeting expectations concerning the curriculum, school culture, and general impressions when attending school [5]. More than half of the respondents' children spend between 5 and 15 minutes on the road to school, which corresponds to the outcomes of other researchers.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…According to the conducted survey, a slightly different response breakdown was obtained based on a variety of obtained factors. When families preferred in-depth knowledge, they confirmed the importance of the quality of successful schools which was manifested by meeting expectations concerning the curriculum, school culture, and general impressions when attending school [5]. More than half of the respondents' children spend between 5 and 15 minutes on the road to school, which corresponds to the outcomes of other researchers.…”
Section: Discussionsupporting
confidence: 61%
“…An increase in the number of learning options results in a loosening of the link between place of residence and the quality of the nearby school [5]. Thus, the everyday mobility of preschool and school-age children becomes particularly relevant.…”
Section: Introductionmentioning
confidence: 99%
“…Posey-Maddox (2014) documented parental involvement strategies among middle-class families in Northern California that unintentionally marginalized longtime low-income families unable to provide the same resources and time, leading to tensions between middleclass and working-class families. Ongoing research in Detroit has revealed more inclusive parental involvement strategies and families who desire a K-12 school pipeline that provides pathways to selective universities (Hill 2018). Middle-class families in Detroit have selected 15 area schools across public, private, and charter entities; they are contributing time and resources, having an integrative effect and driving educational equality.…”
Section: Navigating Policy That Reinforces Equity and Inequitymentioning
confidence: 99%
“…International schools catering largely for local students have been described by Hayden and Thompson (2013) as Type C non-traditional international schools, though some authors in the field question the extent to which some of these schools can actually qualify as international (see Hill, 2016;Bunnell et al, 2016;Poole, 2020). For example Poole (2020), in pointing out that not all Type C schools are the same, refers to a distinct body of what he describes as 'Chinese Internationalised Schools': for-profit Type C international schools in China that are characterised by having a mainly local student body, providing both international and national curricula, and including Chinese symbolic routines.…”
Section: Introductionmentioning
confidence: 99%